On the numerical treatment of the contact problem - Abdallah A. Badr (International Journal of Mathematics and Mathematical Sciences)
The problem of the contact of two elastic bodies of arbitrary shape with a kernel in the form of a logarithmic function—which is investigated from Hertz problem—is reduced to an integral equation. A numerical method is adapted to determine the pressure between the two surfaces under certain conditions.